Computer modeling of digestive processes in the alimentary tract and their physiological regulation mechanisms: closing the gap between digestion models and in vivo behavior - van Aken, George A. (Frontiers in Nutrition, 2024)
A model in development for in silico simulation of digestion and its physiological feedback mechanisms is presented and demonstrated for a few cases. Despite the early stage of development of the model, it already encompasses a large number of processes that occur simultaneously, enabling the prediction of a large number of post-prandial physiological marker that can be highly functional in combination with organ on a chip and digital twin models purposed to measure the physiological properties of organs and the effect of adjusted for composition in normal and diseased states. Because the model is based on known physiology described in the literature, it can be used to get more insight into the complexity caused by the interaction of many simultaneous processes, and for the objective of food development to make predictions regarding the effect of food structure and composition in healthy and diseased states. Input from and collaboration between science fields is needed to further develop and refine the model and to connect with in vitro, in vivo and ex-vivo (organ-on-a-chip) models.